ANALYSIS OF THE INCIDENCE OF GOALS IN THE FIRST ROUND OF FIRST DIVISION OF BRAZILIAN SOCCER CHAMPIONSHIP 2011 (Fiep Bulletin - online, 2012)
Introduction: In Brazil, as in many parts of world, soccer is a national passion. In 1863, representatives from university and clubs from England met at London, with the aim to unify the rules of the soccer game. This soccer evolution, made with the coaches cared more with the tactical aspects of the game. Objective: The aim of the present study is to analyze the incidence of goals in the first turn of the first division of 2011 Brazilian Championship. Methods: Were analyzed 189 matches, for the first round games of the 2011 Brazilian championship, total of 500 goals. Was realized the chi-square test to determine significant differences on the match time and the level of significance was set in p
Keywords: Soccer; Brazil; Incidence